2019
DOI: 10.1002/ehf2.12418
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of hospitalized heart failure patients with preserved, mid‐range, and reduced ejection fractions in Japan

Abstract: Aims There are regional differences in the patient characteristics, management, and outcomes of hospitalized patients with heart failure (HF). The aim of this study was to evaluate the clinical characteristics and outcomes of Japanese patients who are hospitalized with HF on the basis of the left ventricular ejection fraction (LVEF) stratum. Methods and results We retrospectively conducted a multicentre cohort study of 1245 hospitalized patients with decompensated HF be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
85
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 38 publications
(99 reference statements)
22
85
6
1
Order By: Relevance
“…In terms of gender, our patients were predominantly male (62%), which was in concordant to the proportion of male patients in EHFS II (61%) and HIJ-HF II (71%). Less than half of the patients had reduced ejection fraction (23.1%), which is also consistent with proportions reported from studies in the US (46%) [ 28 ] and Japan (36%) [ 31 ]. Interestingly, the character of our study patients was quite different from the data reported by the Thai ADHERE study in 2010 [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…In terms of gender, our patients were predominantly male (62%), which was in concordant to the proportion of male patients in EHFS II (61%) and HIJ-HF II (71%). Less than half of the patients had reduced ejection fraction (23.1%), which is also consistent with proportions reported from studies in the US (46%) [ 28 ] and Japan (36%) [ 31 ]. Interestingly, the character of our study patients was quite different from the data reported by the Thai ADHERE study in 2010 [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…Despite substantial evidence pointing to equivalent outcomes in other settings, patients with HFpEF are often considered at lower risk for mortality compared with their HFrEF counterparts. The present analysis added to this mounting body of literature ( 24 , 25 ), which demonstrated similar outcomes among patients with HFpEF and HFrEF, even in the setting of acute COVID-19. In contrast, our results suggested that patients with HFmrEF could have a better prognosis, because they can represent a distinct and more favorable HF phenotype ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 63%
“…Despite different designs and sample size, the major international studies (CHARM Program, 13 , 14 Framingham Heart study, 15 ESC HF long-term registry, 16 Swedish Heart Failure registry, 17 China Heart Failure Center Registry, 18 and others 19 have demonstrated similar findings. Overall, however, the Saudi patients were younger with a mean age of 62.7 years, as compared with other studies that had a cumulative age range of 65–82 years.…”
Section: Discussionmentioning
confidence: 86%